Functionalization of Silk by AIEgens through Facile Bioconjugation: Full‐Color Fluorescence and Long‐Term Bioimaging. Issue 22 (28th April 2021) - Liu, Chenchen; Bai, Haotian; He, Benzhao; He, Xuewen; Zhang, Jianyu; Chen, Chao; Qiu, Yanping; Hu, Rong; Zhao, Fangxin; Zhang, Yunxiao; He, Wei; Chau, Joe H. C.; et al.
Abstract: Silkworm silk is a promising natural biopolymer for textile and biomedical applications for its remarkable flexibility, excellent biocompatibility and controllable biodegradability. The functionalization of silks makes them more versatile for flexible displays and visible bioscaffolds. However, fluorescent silks are normally fabricated through unstable physical absorption or complicated chemical reactions under harsh conditions. Herein, we developed a simple strategy for preparing fluorescent silks. Five aggregation‐induced emission luminogens (AIEgens) with activated alkynes were synthesized by rational molecular design, and then reacted with silk fibers through facile metal‐free click bioconjugation. The resulting conjugates show bright full‐color emissions and high stability. A white light‐emitting silk was fabricated by simultaneous bioconjugation with red‐, green‐ and blue‐emissive AIEgens. The red‐emissive AIEgen‐functionalized silks were successfully applied for long‐term cell tracking and two‐photon bioimaging, demonstrating great potential for tissue engineering and bioscaffold monitoring. Abstract : Fluorescent silks with full‐color emissions were fabricated through facile metal‐free click bioconjugation with five aggregation‐induced emission luminogens (AIEgens). White light‐emitting silk was prepared and demonstrated potential applications in flexible displays. Moreover, red‐emissive AIEgen‐functionalized silk materials were successfully applied for long‐term cell tracking and two‐photon bioimaging.